KONSTRUKSI METODOLOGIS KITAB SYAJARATU AL-MA’ARIF: Analisis Pemikiran Izzuddin bin Abd Al-Salam - Wahyu Afifurrahman; Fathurrosyid (Program Studi Ilmu Al-Qur’an dan Tafsir, Fakultas Ushuluddin, Universitas Annuqayah (UA), 2022)
Abstract Tafsir and takwil are the results of reading the Al-Quran to determine the relevance of textuality to reality. As a result, a work of interpretation and takwil will never be separated from the horizons that surround the interpreter. This horizon then influences the results of the interpretation and then makes the work subjective-static or objective-dynamic. The book Syajaratu al-Ma'arif wa al-Ahwal is a book of takwil which was popularized by a top student figure, namely Gus Bahauddin Nur Salim, who considered this book to be very argumentative and interesting in taking up urgent values in the Al-Quran. The moral ideals of this book are also full of constructive solutions to the complex problems of the people who are increasingly far from the words ukhwah and rahmah li al-'alamin. This research intends to reveal two problems: First, how is the methodological-epistemological construction of the Tafsir of the book Syajaratu al-Ma'arif wa al-Ahwal. Second, How relevant are Izzuddin's thoughts to harmonizing religious communities in Indonesia? To facilitate this purpose, the author uses era epistemology theory and interpretive methodology theory. The resulting points are: First, the book Syajaratu al-Ma'arif is a book of takwil which is in accordance with the era's epistemological theory and interpretive methodology. Second, there is the relevance of Izzuddin's thoughts to the context of religious harmonization in Indonesia. Keywords: Syajaratu al-Ma'arif, Epistemology, Methodological Construction, Izzuddin bin Abd al-Salam